Superlubricity in EHL Contacts with Water-Containing Gear Fluids - Mustafa Yilmaz; Michael Mirza; Thomas Lohner; Karsten Stahl (Lubricants, 2019)
Fluid friction in elastohydrodynamically lubricated (EHL) contacts depends strongly on the lubricant considered. Synthetic oils can have significantly lower fluid friction than mineral oils. Water-containing fluids have the potential to significantly reduce fluid friction further. The aim of this study is to investigate the film formation and frictional behavior of highly-loaded EHL contacts with water-containing fluids. Comparisons are made with mineral and polyalphaolefin oils. Measurements at an optical EHL tribometer show good lubricant film formation of the considered water-containing gear fluids. Measurements at a twin-disk test rig show coefficients of friction smaller than 0.01, which is referred to as superlubricity, for all considered operating conditions.